Reinforcing Central Government’s Authority over Regional Governments in the System of Indonesian Governance - Ahmad Siboy (Faculty of Law, Universitas Pekalongan, 2022)
Principally, a regional government represents the extended hands of the central government in controlling a regional area. Regional governments are not supposed to run activities not congruent with the policies set by the central government. However, regional governments are often found in contravention of the policies of the central government. This research maps what causes this contravention and the reasons for reinforcing the authority of the central government regarding its connection with regional governments. This research employed normative-juridical methods, statutory, conceptual, and case approaches, revealing that this noncompliance with the central government is sparked by the conditions where a regional head is elected by the members of the public, the president has no right to eject a regional head from his/her tenure, and a regional head is fully authorized to run a regional area, including the regional budgeting. The design of the reinforcement of the authority of the authority of the central government over regional governments is required based on the principle of the unitary state and to guarantee the harmonious policies set by those the regional governments and central government. This design may involve the policy of the central government to take over the governance of regional areas following the deadlock, permit issuance, and the authority of the central government to impose sanctions on regional heads.